Quality and Shelf Life of Spent Broiler Breeder Hen Chicken Koftas Incorporated with Vegetable Dried Powders during Refrigerated Storage - Sharada, M. V. Sneha; Indumathi, J.; Reddy, G. V. Bhaskar; Shakila, S.; Mouli, A. Chandra (International Journal of Bio-resource and Stress Management, 2023)
The present research was carried out in Department of Livestock Products Technology, College of Veterinary Science, Tirupati, Andhra Pradesh, India during July–October, 2022. The objective of this study was to evaluate the shelf life of chicken koftas incorporated with vegetable dried powders each at 4% level under refrigeration (4±1°C) for a period of 20 days on physico-chemical, microbiological and organoleptic quality at an interval of 5 days. The quality parameters were significantly (p<0.05) affected due to incorporation of potato, raw banana and capsicum dried powders and also due to refrigeration storage. The results revealed that there was a significant (p<0.05) increase in the pH, TBARS, Tyrosine and Total plate counts as storage progressed. Psychrophilic and coliform counts were not detected in the control and treated koftas during entire storage period. Yeast and mould counts were not detected on 0th day of refrigerated (4±1ºC) storage in both control and treatments. The counts were detected on 5th day of storage in control and 10th day in treatments and thereafter the counts were increased significantly (p<0.05) in both control and treatments. Sensory evaluation revealed a decrease in the sensory scores with the advancement of storage period. Based on the results, it can be concluded that addition of vegetable dried powders would not only extends the shelf life by protecting the product longer against oxidative rancidity but also had higher acceptability than control and their use in meat products can enhance the shelf life up to 20 days under refrigerated storage without undesirable changes.